Analisis Proses Perumusan CP: Merdeka Mengajar? Analysis of the CP Formulation Process: Independent Teaching? - Eppendi, Jhoni; Ilham, Muhammad; Vega, Nofvia De (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The transformation of education in Indonesia has become a central issue that continues to be discussed in the realm of national education. The government is trying to present a curriculum that is adaptive and relevant to the needs of the times, one of which is by creating the Merdeka Curriculum. Although the Merdeka Curriculum gives teachers greater authority, there is a lack of comprehensive research on how the conversion from CP to ATP impacts the concept of Merdeka Mengajar. This study aims to analyze the process of formulating CP to ATP with the aim of exploring the meaning of "Merdeka Mengajar" in more depth. Using content analysis, this study examines the Merdeka Curriculum documents, especially the process of converting CP to (ATP) in a case study. The Merdeka Curriculum provides space for educators to be creative in learning, but there needs to be a better mechanism to ensure alignment in achieving learning objectives. The flexibility of the Merdeka Curriculum has the potential to increase the relevance of learning, but also poses challenges in maintaining the quality and uniformity of student learning outcomes. The Merdeka Mengajar concept carried by the Merdeka Curriculum is to provide greater autonomy to teachers to plan and implement learning according to the conditions of students in achieving the CP of the curriculum.